Temporal and Spatial Patterns of XCO2 and SIF as Observed by OCO-2: A Case Study in the Midwest Region of Brazil - de Araújo Santos, Gustavo André [UNESP]; Silva, Felipe Facco [UNESP]; De Andrade Águas, Thiago [UNESP]; de Meneses, Kamila Cunha; da Costa, Luis Miguel [UNESP]; da Silva Junior, Carlos Antonio; de Souza Rolim, Glauco [UNESP]; La Scala, Newton [UNESP] (Springer Nature, 2025)
This study aims to examine the seasonal spatial variability of column-averaged of dry air mole fraction of CO2 (XCO2) and Solar induced chlorophyll fluorescence (SIF) in the state of Mato Grosso in the Midwest region of Brazil, employing ordinary kriging (OK) as the spatial interpolation method. The XCO2 and SIF remote sensing data were collected on the Orbiting Carbon Observatory-2 (OCO-2) platform. Descriptive statistical analysis also incorporated spatial variability by using OK on the data that had been segregated into dry and wet seasons. The wet season mean for XCO2 ranged from 393.96 ± 0.10 to 394.14 ± 0.10 ppm between 2015 and 2018, and no variation in the mean of XCO2 was observed between these years in the dry season. SIF was higher in the rainy season compared to the dry season. A significant and more substantial negative relationship (r = − 0.84, p < 0.01) was observed between XCO2 and SIF. Higher values of XCO2 and SIF were observed in the northern region of the state, under the Amazon biome. Therefore, the seasonal variability of XCO2 in the Mato Grosso State, Brazil, is positively related to SIF. It indicates that photosynthesis plays an essential role in this carbon dynamics under regional conditions.
Keywords: Carbon cycle; Carbon–climate feedbacks; Geostatistics; OCO-2